1977
DOI: 10.1002/ijc.2910200209
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of lymphocytes by herpesvirus papio

Abstract: Cotton-topped (CT) or white-lipped (WL) marmoset lymphocytes were transformed in vitro with herpesvirus papio (HVP) into permanently growing lymphoblastoid cell lines (LCL). Five of 9 HVP-transformed CT cell lines contained cells with antigens reacting with antibodies to Epstein-Barr virus (EBV) capsid antigen (VCA) and/or to EBV-induced early antigens (EA). None of 12 WL LCL revealed such antigen-producing cells. Cells from both groups of cultures failed to react with antibodies to the EBV-specified nuclear a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Several lines of evidence suggesting association of this virus with baboon malignant lymphoma were found which paralleled those known for association of EBV and Burkitt's lymphoma. (Rabin et al, 1977;Falk et al, 1977;Deinhardt et al, 1978;Djatchenko et al, 1980). On the other hand in the most representative and thoroughly controlled seroepizootiological study no significant difference was found between anti-HVP titers from the lymphomatous and the healthy baboon groups (Lapin et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggesting association of this virus with baboon malignant lymphoma were found which paralleled those known for association of EBV and Burkitt's lymphoma. (Rabin et al, 1977;Falk et al, 1977;Deinhardt et al, 1978;Djatchenko et al, 1980). On the other hand in the most representative and thoroughly controlled seroepizootiological study no significant difference was found between anti-HVP titers from the lymphomatous and the healthy baboon groups (Lapin et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, many of the defining properties of EBV are conserved in these related LCVs, including immortalization of host B lymphocytes in vitro, establishment of lifelong infection, and induction of diseases similar to those commonly associated with EBV, namely, infectious mononucleosis, lymphoproliferative disease, and lymphomas (8,9,13,37,38). Not surprisingly, the genomes of EBV and the nonhuman primate LCVs characterized to date are colinear and highly homologous with some ORFs displaying striking homology to their EBV counterparts, e.g., the latency-associated proteins EBNA-1 and EBNA-LP and the lytic cycle protein BHRF-1 (56, 61 and 64% amino acid identity, respectively) (18-20, 40, 56).…”
mentioning
confidence: 99%
“…This is understandable, because they carry EBV-related herpesviruses that induce cross-neutralizing antibodies. The EBV-like chimpanzee, baboon, and orangoutan viruses were studied in some detail (26)(27)(28)(29) (33). 14q+ markers were subsequently described in a variety of other lymphoreticular neoplasias (31,(34)(35)(36)(37)(38)(39) We have previously suggested (42) that BL develops in at least three steps.…”
mentioning
confidence: 99%